Perils of the pneumatic tube: how clean are your pods?. Issue 4 (April 2020) - McMullen, P.; Lewis, P.; McGugan, O.; Mortimer, K.
Summary: Pneumatic tube systems (PTSs) are useful features in hospitals for efficient transport of items but further scrutiny reveals their potential risks. We investigated the extent of contamination of pods, used within the PTS with specific alert organisms, namely meticillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE) and carbapenemase-producing Enterobacterales (CPE). Results revealed contamination with VRE (53%) and MRSA (3%), which were reduced to only 3% (VRE) and 0% (MRSA) following disinfection. However recontamination occurred quickly following use. Our findings indicate that PTS could be an efficient method of transfer of potential pathogens around the hospital.